Temporal dynamics in the taxonomic and functional profile of the Sphagnum-associated fungi (mycobiomes) in a Sphagnum farming field site in Northwestern Germany. Issue 11 (5th October 2020) - Borg Dahl, Mathilde; Krebs, Matthias; Unterseher, Martin; Urich, Tim; Gaudig, Greta
ABSTRACT: The drainage of peatlands for their agricultural use leads to huge emissions of greenhouse gases. One sustainable alternative is the cultivation of peat mosses after rewetting ('Sphagnum farming'). Environmental parameters of such artificial systems may differ from those of natural Sphagnum ecosystems which host a rich fungal community. We studied the fungal community at a 4 ha Sphagnum farming field site in Northwestern Germany and compared it with that of natural Sphagnum ecosystems. Additionally, we asked if any fungi occur with potentially negative consequences for the commercial production and/or use of Sphagnum biomass. Samples were collected every 3 months within 1 year. High-throughput sequencing of the fungal ITS2 barcode was used to obtain a comprehensive community profile of the fungi. The dominant taxa in the fungal community of the Sphagnum farming field site were all commonly reported from natural Sphagnum ecosystems. While the taxonomic composition showed clear differences between seasons, a stable functional community profile was identified across seasons. Additionally, nutrient supply seems to affect composition of fungal community. Despite a rather high abundance of bryophyte parasites, and the occurrence of both Sphagnum -species-specific and general plant pathogens, their impact on the productivity and usage of Sphagnum biomass as raw material for growing media was considered to be low. Abstract : Artificial Sphagnum farming sites are surrogate habitats for bog and Sphagnum -specific fungi.